Formulation of nanoemulsions encapsulated with potential anticancer drug, betulinic acid - Abdul Rashid, Nur Nadiah (2014)
The betulinic acid provided was recrystallized in order to obtain high purity compound and was confirmed by spectroscopic analysis. Betulinic acid was incorporated in the oil phase prior to the construction of ternary phase diagram. Phase behaviours of soybean oil and non-ionic surfactants were determined through the construction of ternary phase diagrams. The phase behaviours were affected by hydrophilic-lipophilic balance (HLB) value of surfactants. Higher HLB values produced larger one-phase regions:homogenous and isotropic, in ternary phase diagrams of soybean oil/non-ionic surfactant/deionized water and soybean oil/non-ionic surfactant-co-surfactant/deionized water. The largest one-phase regions were formed by soybean oil/Cremophor EL-Span 20/deionized water formulation. A few compositions with 70% water content were selected on the ternary phase diagram of soybean oil/Cremophor EL/deionized water system as the formulation of emulsions. The selected compositions were 15:15:70, 18:12:70, 21:9:70 and 24:6:70. The first set of emulsions was prepared via low-energy emulsification method, while the other set was formulated via high-energy emulsification method using a high-pressure homogenizer with homogenizing cycle of 2, 4, 6 and 8. Characteristics of emulsions were studied. The average particle size of low-energy formulated emulsions was larger than 130 nm at week 1 and the size increased rapidly throughout 12-weeks of study while for emulsions formulated via 8 homogenizing cycles, the average particle size was below 57 nm at week 1 and remained below 100 nm after 12-weeks. Formulation of 24:6:70 produced the smallest average size which was 59 nm. The surface charge values for all formulations with betulinic acid were more negative than -26.7 mV which indicates moderate stability of the emulsions. The stability of emulsions was also studied via visual observation for 6 months. All high-energy formulated emulsions were still in one phase without any separation of layers observed. The pH values were between 3.9 to 4.1 for all formulations. Betulinic acid can still be detected by HPLC-RI detector in the selected 24:6:70 formulation even after 6 months of storage.